NUDGE VERSUS BOOST: A DISTINCTION WITHOUT A NORMATIVE DIFFERENCE. (23rd August 2018) - Sims, Andrew; Müller, Thomas Michael
Abstract: Behavioural public policy (BPP) has come under fire by critics who claim that it is illiberal. Some authors recently suggest that there is a type of BPP – boosting – that is not as vulnerable to this normative critique. Our paper challenges this claim: there's no non-circular way to draw the distinction between nudge and boost that would make the normative difference required to infer the permissibility of a policy intervention from its type-membership. We consider two strategies: paradigmatic examples and causal mechanisms. We conclude by sketching some suggestions about the right way to approach the normative issues.